Beyond the scars: a qualitative study on the experiences of mastectomy among young women with breast cancer in a country with crisis - Shaza Hasan; Keng Sheng Chew; Rekaya Vincent Balang; Shirly Siew Ling Wong (BMC, 2023)
Abstract Background As breast cancer incidence rises among younger women, there is a knowledge gap regarding the emotional, physical, and social effects of mastectomy, specifically in a crisis-affected country such as Syria. This study aimed to explore these effects on young women with breast cancer in Syria, taking into consideration the cultural significance of a woman's breast as part of her feminine identity. Methods A qualitative design, using semi-structured in-depth interviews with 10 young women with breast cancer who underwent mastectomy, was conducted between June to December 2022. Results Thematic analysis was used to analyze the data, and five main themes were identified: (1) psychological and emotional well-being (altered self-esteem and femininity, impact on sexual life and relationships, psychological distress associated with mastectomy, mirror trauma and the need for psychological care); (2) body image and breast reconstruction (the dilemma over reconstruction decision, body image and clothing and lack of access to prosthetic information/services); (3) social and interpersonal factors (lack of marriage choices and society's view and stigma); (4) coping mechanisms with mastectomy effects (family support; faith in god almighty; comparing their situation to others and use of prosthetics) and (5) physical health and functioning (physical effects on mobility and function). Conclusion Mastectomy has significant physical, emotional, and social consequences on young women with breast cancer, particularly in crisis-affected Syria where access to breast reconstruction is limited. It is crucial for healthcare professionals to understand these impacts, to raise awareness, encourage early detection, and promote less aggressive treatments to improve women's quality of life.